Digital Education Management in Improving the Quality of Technology-Based Learning - Bhoki, Hermania; Bani, Benediktus (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to explore the role of digital education management in improving the quality of technology-based learning. Specifically, it examines how educational leadership, managerial practices, and stakeholder engagement influence the integration and effectiveness of digital tools in educational settings. Method: A qualitative literature review was conducted using library research, synthesizing findings from academic sources published between 2019 and 2025. The study analyzed key themes, including barriers to technology integration, the impact of managerial practices, and the role of stakeholder involvement in digital education management. Results: The study found that educational leadership plays a pivotal role in digital transformation by providing strategic direction and fostering collaborative decision-making. Key barriers to effective integration included resistance to change, lack of digital literacy, and infrastructure limitations. Additionally, professional development for educators and active stakeholder engagement were identified as critical factors for the success of technology-based learning. The study also highlighted the positive effects of personalized learning and increased accessibility facilitated by digital tools. Novelty: This study contributes to the understanding of digital education management by emphasizing the interconnected roles of leadership, resource management, and community involvement in successfully integrating technology into education. The research also offers insights into overcoming barriers and suggests future directions for sustainable digital education practices and innovative teacher training models.